School libraries in Spain facing a new decade - Gómez-Hernández, José-Antonio (Anuario ThinkEPI, 2010)
The article presents an overview of the situation of school libraries in Spain, and suggests that, like the university library has become a resource center for learning and research, the school library could become also a resource center for learning and teaching, acting as a dynamizer and catalyst for the life of schools.
Keywords: Library; School libraries; Schools.